Influence Mechanisms of Rainfall and Terrain Characteristics on Total Nitrogen Losses from Regosol - Xiaowen Ding (Water, 2017)
The upper reach of the Yangtze River is an ecologically sensitive region where water loss, soil erosion, and nonpoint source (NPS) pollution are serious issues. In this drainage area, regosol is the most widely distributed soil type. Cultivation on regosol is extensive and total nitrogen (TN) has become a common NPS pollutant. Artificial rainfall experiments were conducted to reveal the influence mechanisms of rainfall and terrain on TN losses from regosol. The results showed that there were positive correlations between precipitations and TN loads but negative ones between precipitations and TN concentrations. Furthermore, negative correlations were more obvious on fields with slopes of 5° and 25° than on other slopes. With increasing rainfall intensity, TN loads rose simultaneously. However, TN concentration in runoff-yielding time presented a decline over time. As far as terrain was concerned, TN loads grew generally but not limitlessly when slopes increased. Similarly, TN concentrations also rose with rising slopes; upward trends were more obvious for steeper slopes. Furthermore, the initial runoff-yielding time became longer for steeper slopes and the differences under various rainfall intensity conditions diminished gradually.